Роль BRAF-мутацій у визначенні прогнозу папілярного раку щитоподібної залози - Хоперія, В. Г. (Clinical Endocrinology and Endocrine Surgery, 2011)
The purpose of this multicenter study was to investigate the prognostic significance of BRAF mutations in patients with papillary thyroid carcinoma (PTC). According to the results of multiple analysis of our research, supplemented by various amounts of sample, mixed risk factors, different compositions of PTC subtypes confirmed BRAF mutation with high-risk subtypes of PTC and its role in the formation and progression of PTC. We also demonstrated the relationship of BRAF mutation recurrent PTC, even in patients at an early stage but with high tumor aggressiveness. Thus, BRAF mutation is a new prognostic marker, which complements the existing traditional prognostic factors of PTC used. Determination of BRAF mutations in thyroid aspirate needle units will conduct risk stratification of PTC in the preoperative stage. Characteristics of BRAF mutations may contribute to both primary treatment and long-term monitoring of recurrent disease in patients with PTC.